2018
DOI: 10.3389/fpsyg.2018.00728
|View full text |Cite
|
Sign up to set email alerts
|

Visual Speech Perception Cues Constrain Patterns of Articulatory Variation and Sound Change

Abstract: What are the factors that contribute to (or inhibit) diachronic sound change? While acoustically motivated sound changes are well-documented, research on the articulatory and audiovisual-perceptual aspects of sound change is limited. This paper investigates the interaction of articulatory variation and audiovisual speech perception in the Northern Cities Vowel Shift (NCVS), a pattern of sound change observed in the Great Lakes region of the United States. We focus specifically on the maintenance of the contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…McGuire and Babel (2012) argue that visual cues contribute to perceptual asymmetry for /f/ and /h/, while King and Chitoran (2022) argue that the distinct visual quality of British labiodental /r/ (i.e., [V]) helps to distinguish this variant from /w/. Most relevant to the present study, Havenhill and Do (2018) argue that visual perceptibility of lip rounding has contributed to the preservation of rounding on /O/ as it undergoes fronting as part of the Northern Cities Shift (NCS). In contrast to the fronting of /u/, fronting of /O/ in the NCS is not driven by coarticulation, but by pressure to maintain dispersion within the vowel space (Labov, 1994).…”
Section: Discussionmentioning
confidence: 80%
“…McGuire and Babel (2012) argue that visual cues contribute to perceptual asymmetry for /f/ and /h/, while King and Chitoran (2022) argue that the distinct visual quality of British labiodental /r/ (i.e., [V]) helps to distinguish this variant from /w/. Most relevant to the present study, Havenhill and Do (2018) argue that visual perceptibility of lip rounding has contributed to the preservation of rounding on /O/ as it undergoes fronting as part of the Northern Cities Shift (NCS). In contrast to the fronting of /u/, fronting of /O/ in the NCS is not driven by coarticulation, but by pressure to maintain dispersion within the vowel space (Labov, 1994).…”
Section: Discussionmentioning
confidence: 80%
“…Directly after stimulus presentation, participants identified the word-initial consonant they perceived by clicking on a word from two options using a wireless optical mouse. A 2 000 ms time limit was imposed on responses, after which the program automatically advanced to the next stimulus (as in Havenhill and Do, 2018). Subjects were instructed that their first mouse click would be recorded and were asked to respond as quickly and accurately as possible.…”
Section: Methodsmentioning
confidence: 99%
“…and [n], may maximize the perceptual distinctiveness of these sounds, which may explain why they occur so frequently cross-linguistically, despite their relatively similar acoustic cues (Dohen, 2009). In a production and audio-visual perception study of the American English /O/-/A/ contrast, which is currently undergoing a merger in some dialects, it was found that a visual labial contrast was retained, despite the merging acoustics (Havenhill and Do, 2018). The authors themselves argued that visual cues may play a role in the shaping of phonological systems by inhibiting misperception of the speech signal in cases where two sounds are acoustically similar.…”
Section: B Towards An Audio-visual Enhancement Hypothesismentioning
confidence: 99%
“…Indeed, speech has been shown to be visually optimised in cases where pressure to maintain a phonological contrast is high. For example, Havenhill & Do (2018) observed that in American English, the visual lip rounding cue enhances perception of the /A/-/O/ contrast, and Traunmüller & Öhrström (2007) found that in Swedish, listeners rely on visual cues in the perception of /i/-/y/. Future research could consider whether the different visual cues for /r/ and /w/ are perceptibly salient to Anglo-English speakers.…”
Section: Accounting For the Labial Gesture In Anglo-english /R/mentioning
confidence: 97%